Trends in home enteral nutrition at a tertiary teaching hospital: 2005–2013. Issue 3 (13th March 2015) - Parker, Elizabeth Kumiko; Faruquie, Sahrish Sonia; Talbot, Peter
Abstract Aim There are limited data on home enteral nutrition patients in NSW because of the lack of a state‐wide or national registry in Australia. The present study aimed to report on the trends in home enteral nutrition at a tertiary teaching hospital in NSW Australia, from 2005 to 2013. Methods A 9‐year retrospective study (2005–2013) on the trends of home enteral nutrition was performed by retrieving data from a database set up specifically for home enteral nutrition patients at the study hospital. Results The number of home enteral nutrition patients at the study hospital is increasing; however, the rate of expansion has slowed down. Mean age ranged from 52.3 to 55.7 years during the study period and the most common primary diagnosis of patients remained cancer, non‐malignant respiratory disease and neurological disorders. Over time there has been a notable increase in patients requiring oral nutrition support, and a corresponding decrease in patients requiring enteral tube feeding. Gastrostomy tubes remained the most common type of enteral access device for tube fed patients; however, an increase in jejunostomy tubes was observed. Death was the principal reason for discharge from the service followed by completion of home enteral nutrition. Conclusions The use of home enteral nutrition has increased in the last 9 years at the study hospital. Most patients were registered for oral nutrition support and had an underlying cancer diagnosis, which may have contributed to the high rate of death observed in this patient population.